Pengaruh Digital Competence dan Knowledge Sharing terhadap Service Quality dengan Adaptive Performance Sebagai Mediasi pada Teknisi Broadband PT. Telkom Akses Witel Surabaya - Moch Irsyad Ainur Rafi; Fajar Wicaksono; Siti Mujanah; Made Suparta (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to examine the effects of Digital Competence and Knowledge Sharing on Service Quality, with Adaptive Performance serving as a mediating variable among broadband technicians at PT. Telkom Akses Witel Surabaya. This research employed a quantitative approach using an explanatory research design. Data were collected through questionnaires distributed to 113 broadband technicians selected using a purposive sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that Digital Competence has a positive and significant effect on both Service Quality and Adaptive Performance. Knowledge Sharing also has a positive and significant effect on Adaptive Performance; however, it does not directly influence Service Quality. Furthermore, Adaptive Performance was found to have a positive and significant effect on Service Quality. The mediation analysis indicates that Adaptive Performance partially mediates the relationship between Digital Competence and Service Quality and fully mediates the relationship between Knowledge Sharing and Service Quality. These findings suggest that improving service quality depends not only on employees’ digital competencies and knowledge-sharing practices but also on their ability to adapt to technological changes and dynamic work demands. Therefore, organizations should strengthen digital competence, encourage knowledge-sharing activities, and enhance employees’ adaptive capabilities to improve service quality and organizational performance.